Adoption of measures of the precaution in the teaching care practice by health care workers team: perceptions and limitations - Adriana Cristina Oliveira; Thabata Coaglio Lucas (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
It was aimed at knowing the participation of the professionals in training about infections hospitals, cognitives and behavior aspects to adoption of the precaution and a perception regarding the activities that designates the CCIH. It was a descriptive study carried out in a public hospital in the period from july to November 2006. 159 health care workers took part of the study: 59,1% nursing technicians, 18,9% physicians,13,8% nurses, 5,0% nursing auxiliaries and 3,1% physiotherapeutics. It was verified that for 37,7% of the professionals the CCIH promotes training, but 56,6% never took part on them; 90,6% admitted the indication of the handwashing, however only 46,5% had known the type of the EPI to be used in the colonized patient healthcare and just 17% the type of the precaution to be established for this patient. Concerning the activities that designates the CCIH it was distinguished the training of the professionals and the infections control; the non-adoption of precautions among the professional was justified by inadequate training and knowledge lack. This study contributes for redefinition of the training strategies together the healthcare workers team, favouring the attention for precautions recommendations during the care.